Entertainment VS. Education: Students’ Perspectives on the Use of Apps - Zuraina, Ali; Nurul Nadia, Muhammad; Hafizoah, Kassim; Siti Norzaimalina, Abd Majid; Rosnani, Ismail; Mohd Amir Izuddin, Mohamad Ghazali; Supyan, Hussin; Ahmad Fauzi, Ayob (2015)
The use of mobile application also known as apps is fast becoming a trend in education since it offers users fun and entertaining learning experiences. Weighing similarly important, a particular app should also offer educational opportunities to its users. The current study attempts to investigate the students’ perceptions on these two perspectives of using mobile application among students at the tertiary level education. A focus group discussion was conducted on 13 international students taking Preparatory Intensive English course in one of the university in the East Coast of Malaysia. The findings of the study revealed that an app may facilitate learning. For optimal use of app, entertainment features i.e. videos need to be integrated in the app to ensure that students can learn and play at the same time. Last but not least, multimodal texts need to be integrated in developing a language learning app to sustain students’ learning motivation.